Perceptions about screening for prostate cancer using genetic lifetime risk assessment: a qualitative study - Pia Kirkegaard; Adrian Edwards; Trine Laura Overgaard Nielsen; Torben Falck Ørntoft; Karina Dalsgaard Sørensen; Michael Borre; Flemming Bro (BMC Family Practice, 2018)
Abstract Background Most health authorities do not recommend screening for prostate cancer with PSA tests in asymptomatic patients who are not at increased risk. However, opportunistic screening for prostate cancer is still wanted by many patients and it is widely used in primary care clinics, with potential for overdiagnosis and overtreatment. Better tools for risk assessment have been called for, to better target such opportunistic screening. Our aim was to explore perceptions about prostate cancer risk and subsequent opportunistic screening among patients who were not at increased risk of prostate cancer after a first PSA test plus a genetic lifetime risk assessment. Methods We undertook semi-structured patient interviews with recording and verbatim transcription of interviews. Data were analysed thematically. Results Three themes were identified: uncertainty of the nature of prostate cancer; perceived benefits of testing; and conflicting public health recommendations. Prostate cancer was spoken of as an inescapable risk in older age. The aphorism “you die with it, not from it” was prominent in the interviews but patients focused on the benefits of testing now rather than the future risks associated with treatment relating to potential overdiagnosis. Many expressed frustration with perceived mixed messages about early detection of cancer, in which on one side men feel that they are encouraged to seek medical testing to act responsibly regarding the most common cancer disease in men, and on the other side they are asked to refrain from opportunistic testing for prostate cancer. Taken together, personal risks of prostate cancer were perceived as high in spite of a normal PSA test and a genetic lifetime risk assessment showing no increased risk. Conclusion Patients saw prostate cancer risk as high and increasing with age. They focused on the perceived benefit of early detection using PSA testing. It was also commonly acknowledged that most cases are indolent causing no symptoms and not shortening life expectancy. There was a frustration with mixed messages about the benefit of early detection and risk of overdiagnosis. These men’s genetic lifetime risk assessment showing no increased risk did not appear to influence current intentions to get PSA testing in the future.